(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Nowadays, capacitive power transfer (CPT) is becoming increasingly popular technology in the wireless charging field due to its better mobility and higher durability. This paper proposed a CPT system by using Class-E inverter. This topology is selected due to its ability to achieve 100% efficiency theoretically. L-match impedance matching circuits are applied at both transmitter and receiver part to allow the load impedance to match with the source impedance to maximize the power transfer. The proposed CPT system is designed and simulated by using Simulink in MATLAB software. Its output performances are analyzed. Besides, the designed CPT system is used to investigate the factors that affect its output performance by varying the load, duty cycle and gap distance between coupling plates. From this work, the proposed CPT system produced up to 97.35% efficiency and output power of 10W.